Advances in Synthesis and Potentially Bioactive of Coumarin Derivatives - Anamika; Utreja, Divya; Ekta; Jain, Nisha; Sharma, Shivali (Current Organic Chemistry, 2018)
Although, numerous antimicrobial agents have been reported by the scientists to control fungal and bacterial diseases, but due to less cost effectiveness, non-availability and environmental hazardous of existing antimicrobial agents, there is still a need to synthesize new class of antimicrobial agents to control microbes effectively. Coumarin, a heterocyclic compound containing oxygen in its scaffold, acts as a building block for large number of biologically active compounds and is known to possess variety of biological activities viz. antiviral, antimicrobial, anticonvulsant, anticancer analgesic and antiinflammatory. This review mainly focuses on various methods related to synthesis of coumarin derivatives and its biological activity as antimicrobial.
Keywords: Coumarin